Development of an Experimental Lunar Volatiles Extraction System - Olson, Aaron (Proceedings of the Wisconsin Space Conference, 2018)
The Helium Extraction & Acquisition Testbed (HEAT) is an experimental lunar volatiles extraction system designed to test recuperative heat pipe heat exchanger (HPHX) technology that could be used to release volatiles from lunar regolith. HEAT has passive and active granular flow components that allow for the controlled flow of regolith through a variety of HPHX configurations. HEAT has instrumentation to measure regolith and heat pipe temperature at key positions in the device to ascertain the HPHX recuperative efficiency of the device. Volatile gas release is also measured with the use of a residual gas analyzer. The primary volatile of interest for this investigation is helium-3 (3He). As a surrogate for 3He containing regolith, 4He containing JSC-1A regolith simulant is used. A summary of the design of the HEAT device and an overview of the modeling approach for an HPHX will be discussed in this paper.